Endogenous selection into single and coauthorships by surname initials in economics and management - David Ong; Ho Fai Chan; Benno Torgler; Yu (Alan) Yang (Center for Research in Economics, Management and the Arts (CREMA), 2015)
Many prior studies suggest that alphabetic ordering confers professional advantages on authors with earlier surname initials. However, these studies assume that authors select into coauthorships without regard to the incentives identified. We consider the alternative and develop a model of endogenous selection into single and coauthorships for economics, which uses alphabetical ordering. We then tested it with authorship data from economics, with management (which does not use alphabetical ordering) as a benchmark. We predicted that lower "quality" authors with earlier surnames would be less desirable as coauthors, while higher quality authors with later surnames would have a lower desire to coauthor. Both types of authors are therefore more likely to single- author. Furthermore, higher quality authors with earlier surnames should have more and better coauthoring options. Consistent with our predictions, we found citation ranks were increasing on surnames for single-authored works and decreasing for coauthored in economics, both absolutely and compared to management. Also as predicted, this effect is driven by lower-tier journals in which there is likely a thinner market for coauthors. Furthermore, comparing citation ranks of first-authors of alphabetical and nonalphabetical papers shows that the "larger share" effect of being first is dominated by the "smaller pie" effect of selection from second authors who will accept a smaller share.
Keywords: J01; J15; J44; 330; alphabetic order effect; citations; coauthorships; endogenous teams; contests